Maternal biosocial factors influencing new born birth weight at a municipal corporation maternity home in Bangalore city - Konapur, Kavita S.; Srikanth, Jayanthi (International Journal Of Community Medicine And Public Health, 2017)
Background: Birth weight of new born is known to be influenced by several maternal biosocial factors. The study was undertaken to find association of various maternal biosocial factors influencing birth weight of the new born. Methods: The study subjects were 150 postnatal women and their new born delivered in an Urban Municipal Corporation Maternity Home. Study subjects were chosen by purposive sampling. Socio demographic and pregnancy related information was collected by interview method and from antenatal records. Results: The proportion of low birth weight noted was 8.6%. Statistically significant association was noted between new born birth weight and maternal health status during pregnancy which includes weight gain during pregnancy, intake of iron and folic tablets and antenatal check-up. Maternal haemoglobin levels had a positive correlation with new born birth weight. Conclusions: Maternal health is vital for new born wellbeing. Birth weight of new born has shown steady improvement over a period of time and this is as a result of availability of better maternal health care services in urban corporation maternity home.